Competing (ac)counts of disability: situating prevalence studies in Zambian disability policymaking - Cleaver, Shaun; Lencucha, Raphael; Bond, Virginia; Hunt, Matthew (Disability Studies Quarterly, 2023)
Research is a critical starting point for public policy. For disability policy, the calculation of prevalence – the percentage of persons with disabilities in a population – has attracted significant attention. Multiple disability prevalence studies have been conducted in Zambia. We used data from semi-structured interviews about research and the policy process with twelve Zambian disability policy stakeholders to explore perspectives about disability prevalence research and policymaking. Policy stakeholders, disability advocates and policymakers, expressed more interest in prevalence than in other types of research. Participants perceived prevalence research according to three competing priorities: inclusion (‘Involve us [for] good results’), pragmatism (‘We have to use that [number]’), and granularity (‘We need details’). Participants discounted the value of prevalence research that conflicted with their priorities. Better understanding of stakeholder perspectives of disability prevalence can illuminate ways that these perspectives influence the use of research evidence in disability policy making.